Quando a diferença assume uma marca, uma sentença, um destino : configurações da periculosidade dos delitos de doentes mentais nos inquéritos policiais de Mato Grosso (1930-1958) - Morgado, Eliane Maria Oliveira (2018)
From this research, it is seeked to contribute with the studies about the mentally ill people in conflict with the law. To do so, it was investigated the dangerous behavior patterns of mentally ill people in police investigations in Mato Grosso. Established a time-frame between 1930 and 1958, marked by a dialogue with the historiography and the documentary scope, this research is guided considering the articulations between the modernist Vargas speech and the public health policies engendered for mental illness and psychiatry, as well as the intersections between the medical-psychiatric speech and the legal discourse. In order to establish a dialogue with the analyzed documents, It is used the studies produced by Michel Foucault (1926-1984) in his books, courses, and texts, focusing on his work as a whole, those focused on understanding social discourses and practices about madness. It is highlighted among them, History of Madness, Abnormal (1974- 1975), the lecture given in the city of Toronto in October 1977 on the Evolution of the notion of "dangerous individual" in the Legal Psychiatry of the XIX century and the book Truth and juridical Forms, whose conferences were held in Brazil in 1973. This research is limited to the investigation of two police cases, two mental health examinations and a request for the conditional release of individuals who had committed crimes under the light of the Criminal Code of 1940, that is, immersed in the logic of criminal liability. After the construction of the theoretical reference, and the analysis of the studied documents, it was possible to verify that the issue of dangerousness, although in a firstlook it is relegated to the legal universe, it is not limited to this one, since the evaluations of the expert doctor are presented as fundamental elements to whom was to assist the judge when there was suspicion of insanity. Thus, a process of intercession between the medical examination and the judicial practices was formed, which were located beyond the literality of the law. In this way, it was common to verify by means of examinations, that the individual was at once mad, and incapable of answering for criminal offenses. Despite being submitted to psychiatric medical evaluation to prove his insanity, the verdict was up to the judge. In Mato Grosso, it was possible to verify that the institution of seclusion, between the decades of 1930 and 1958, did not use methods focused on the cure of the individuals, but in the imprisonment of the dangerousness, through his/her total psychic neutralization, locking his/her in the first institutional space destined to the prison of the madness - Asilo de Alienados do Coxipó da Ponte. This institution was not only a place that housed the poor, the stray and the alienated ones, but it was also constituted as the embryo of the Judicial Asylum in Mato Grosso: to this place, there were also sent the mentally ills who committed crimes, but it was not excluded the practice of confinement of persons who committed the criminal offense in jail. Just like this, decades would passed until the institutionalization of madness and decades would passed for people waiting in the Judicial Asylum